2021
DOI: 10.3390/ma14185260
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Properties and Salt Spray Corrosion Test Parameters Optimization for AA8079 with Reinforcement of TiN + ZrO2

Abstract: This work mainly focuses on increasing the mechanical strength and improving the corrosion resistance of an aluminum alloy hybrid matrix. The composites are prepared by the stir casting procedure. For this work, aluminum alloy 8079 is considered as a base material and titanium nitride and zirconium dioxide are utilized as reinforcement particles. Mechanical tests, such as the ultimate tensile strength, wear, salt spray corrosion test and microhardness test, are conducted effectively in the fabricated AA8079/Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In addition, in Ref. [14] the marble production system in Italy was studied, and it was reported that the highest burdens came from the marble quarrying operations due to the massive amount of fossil fuels and electricity consumption; furthermore, the marble production system emitted CO 2 , SO 2 , NOx, non-volatile organic compounds (NMVOC), and heavy metals [14,30,31]. Among the nine (09) environmental impacts caused by the marble production chain, [15] found the highest contribution of the marble tile production chain to GWP, AP, EP, and HT in Italy, which is in line with the results of the present study conducted in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in Ref. [14] the marble production system in Italy was studied, and it was reported that the highest burdens came from the marble quarrying operations due to the massive amount of fossil fuels and electricity consumption; furthermore, the marble production system emitted CO 2 , SO 2 , NOx, non-volatile organic compounds (NMVOC), and heavy metals [14,30,31]. Among the nine (09) environmental impacts caused by the marble production chain, [15] found the highest contribution of the marble tile production chain to GWP, AP, EP, and HT in Italy, which is in line with the results of the present study conducted in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this, thermogravimetric (TG) analysis were used in the present investigation for thermal analysis using STA 409 PL Luxx instrument. In which, a mass of the sample is measured while varying the sample temperature to provide information about various physical phenomena such as desorption, adsorption, absorption and phase transition and about chemical phenomena such as solid-gas reactions, thermal decomposition and chemisorption [25][26][27][28][29][30]. Various samples of 10 mg were kept on the platinum pan where temperature was increased from 30 °C to 550 °C.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Globally, there has been a focus on biofuels, particularly those derived from crops such as corn, sugarcane, and soybeans, which are regarded as renewable energy sources by some experts. Wood and crop leftovers are also used as a biofuel [8,9]. Alternative energy sources that are nearby available, particularly renewable, and ecologically beneficial by helping CO 2 balance should be investigated and used to meet energy demands [10,11].…”
Section: Introductionmentioning
confidence: 99%